ANALISIS PENDAPATAN USAHA TANI JAGUNG MANIS AMINDUK DI KEBUN SHOW WINDOWS DESA KEMBUAN KECAMATAN TONDANO UTARA - Lydia Ch. Porotu'o; Celcius Talumingan; Ellen G. Tangkere; Melissa L.G. Taroreh (COCOS, 2013)
ABSTRACLydia Christianty Porotu'o, Farming Income Analysis of AmindukSweet Corn Kembuan Village, North Tondano Sub District. Under GuidanceIr. Celsius Talumingan, MP as Chairmain , Ellen G. Tangkere, SP, Msi andMelissa L.G. Taroreh, SP, Msi as members.The Objective of this research is to know the sweet corn farm incomeKembuan Village, North Tondano Sub District. This study uses primary data andsecondary data. Primary data obtained through direct interviews to farmersfarmers and entrepreneurs with observation techniques to observe directly the areaof aminduk sweet corn, while the secondary data obtained from the kembuanvillage profile report format, and Web sites related to the kembuan village northtondano sub district of aminduk sweetcorn. Data analysis method used in thisresearch is descriptive, by calculating the total revenue, cost of production, totalrevenue to total revenue and comparison ratsio R / C.The results of this research of aminduk sweetcorn showed that farmingincome analysis Civil Registration sweet corn produce comparison ratio R / C 3,1it can be interpreted that their farming is visible to be developed. This is becausethe calculation of farming revenue was relatively big that revenue in biggerincome.Based on these results it can be concluded that the Farming IncomeAnalysis of Aminduk Sweet Corn Kembuan Village, North Tondano Sub Districtcan be cultivated, by continuing to improve yields due to high consumer demandin the community. Although the results are promising revenue is considered to bea guarantee to continue farming Farming Income Analysis of Aminduk SweetCorn Kembuan Village, North Tondano Sub District sweet corn productionsystems although costly due to apply the techniques and technologies that aredifferent from usual. Therefore recommended to farmers around the kembuanvillage, North Tondano Sub district to consider this as an alternative employmentopportunity to improve well-being, so that the farmers around village becomesmallholder farmers not only immigrants farmers.